Two-stage coalition formation and radio resource allocation with Nash bargaining solution for inband underlaid D2D communications in 5G networks. (1st June 2018) - Tseng, Chih-Cheng; Shih, Jyun-Yao
Abstract: For D2D communications in the inband underlaid 5G networks, to improve the utilization of cellular uplink spectrum, a two-stage coalition formation and resource allocation scheme is proposed to allocate the radio resources based on the numbers of resource blocks (RBs) requested by D2D pairs. Any set of D2D pairs whose pairwise distances longer than a threshold value are organized into a Stage-1 coalition by the Bron-Kerbosch algorithm. Otherwise, they are organized into Stage-2 coalitions based on the total number of RBs they requested. Since D2D pairs in a Stage-1 coalition are far away from each other, the co-channel interference can be ignored. To improve the RB utilization, RBs that can be used by D2D pairs in the same Stage-1 coalition are first allocated to that Stage-1 coalition. Then, based on the total number of RBs requested by D2D pairs in a Stage-2 coalition, RBs are allocated to Stage-2 coalitions. Since RBs allocated to a Stage-2 coalition cannot be shared by D2D pairs in that Stage-2 coalition, the Nash bargaining solution (NBS) is used to further allocate RBs to D2D pairs in that Stage-2 coalition. Simulation results show that, the proposed two-stage coalition formation and resource allocation scheme allocates more number of equivalent RBs to D2D pairs than the number of RBs allocated by the greedy algorithm. Specifically, based on the simulation results, the total number of equivalent RBs allocated by the proposed scheme can be up to 325.52% of that allocated by the greedy algorithm.